Women in the History of edition in Argentina: ¿Is edition having gender marks? (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2019)
The publishing area in Argentina has its origin between the 19th and the 20th century, when some publishers developed with significant particularities. Some others were created later. Overtime, women editors made their own contributions to the editorial industry; however, when we think about emblematic editors, the feminine figures remain hidden. Where are their traces? Our challenge here is to turn some of them clearly visible.This work is not intended to focus on the women publishers’ space as a separate gendered space, centered on the particular interests of a female audience. Rather we try to explore how these women editors have been able to create public voices, participate in the public debate and act as agents of change beyond their immediate sphere of influence. We point out in the different cases, those interstices that allowed them to build their own lives and their editorial work. Each of them has arrived to edition in some particular way, bypassing stereotypes, for others or for themselves, in various different ways.In this sense, we analyze some cases of women editors in the passage from the 20th century to the 21st century, taking into account the historical background. For this purpose, we have reviewed sources, such as institutional reports, analyzed in other contexts, and created new ones based on the construction of oral sources
Keywords: Women editors; Invisible feminine figures; History of edition in Argentina; History of women; Women's life histories